2021
DOI: 10.1002/lpor.202000450
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Points as Lasing Prethresholds

Abstract: The genesis of lasing, as an evolution of the laser hybrid eigenstates comprised of electromagnetic modes and atomic polarization, is considered. It is shown that the start of coherent generation at the laser threshold is preceded by the formation of a special hybrid state at the lasing prethreshold. This special state is characterized by an enhanced coupling among excited atoms and electromagnetic modes. This leads to an increase in the rate of stimulated emission in the special state and, ultimately, to lasi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…[19] EPs can enhance lasing emission and allow to control the lasing directivity. [18,20,21] Recently, it was also shown that EPs provide the enhanced local density of the states (LDOS), scaling with a square of the Purcell factor. [22,23] If EPs appear on a polariton branch, this causes a strong enhancement of the boson scattering probability to this state, which can lead to the polariton accumulation in a nonlinear regime, resulting in the polariton lasing.…”
Section: Introductionmentioning
confidence: 99%
“…[19] EPs can enhance lasing emission and allow to control the lasing directivity. [18,20,21] Recently, it was also shown that EPs provide the enhanced local density of the states (LDOS), scaling with a square of the Purcell factor. [22,23] If EPs appear on a polariton branch, this causes a strong enhancement of the boson scattering probability to this state, which can lead to the polariton accumulation in a nonlinear regime, resulting in the polariton lasing.…”
Section: Introductionmentioning
confidence: 99%
“…In these systems, the EP separates areas of parameter space with PT-symmetric and non-PT-symmetric eigenstates 4 7 . Other examples of non-Hermitian systems with an EP include strongly coupled cavity-atom systems 3 , 8 , polariton systems 9 11 , two dimensional lattice systems 12 , 13 , optomechanical systems 14 , 15 , and even conventional laser systems 16 . Non-Hermitian systems with EPs have a number of unique properties, due to which they have found many applications 3 , 4 , 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The systems in the state close to the EP demonstrate enhanced sensitivity to external perturbations and thus can be used for the EP-based sensors [18][19][20] and laser gyroscopes [21,22]. The EPs can be associated with the laser threshold [23,24] and find use in realization of specific lasing conditions [25][26][27]. Besides the isolated EPs, some non-Hermitian systems support the lines of EPs [28] or even the exceptional surfaces [29] which can be utilized for sensitivity enhancement as well [30,31].…”
Section: Introductionmentioning
confidence: 99%